Evaluation of prenatal risk factors for prediction of outcome in right heart lesions: CVP Score in fetal right heart defects. (September 2014) - Neves, Ana Luisa; Mathias, Leigh; Wilhm, Marilyn; Leshko, Jennifer; Linask, Kersti K.; Henriques-Coelho, Tiago; Areias, José C.; Huhta, James C.
Abstract Objective: To determine the prenatal variables predicting the risk of perinatal death in congenital right heart defects. Methods: Retrospective analysis of 28 fetuses with right heart defects was performed. Logistic regression analyses were performed to obtain odds ratios (OR) for the relationship between the risk of death and echocardiographic parameters. The parameters that correlated with the outcome were incorporated in an attempt to devise a disease-specific cardiovascular profile score. Results: Fetal echocardiograms (143) from 28 patients were analyzed. The cardiovascular profile score predicted the risk of death. A lower right ventricle (RV) pressure was associated with mortality (OR 0.959; 95% confidence intervals (CI) 0.940–0.978). Higher peak aortic velocity through the aortic valve (OR 0.104; 95% CI 0.020–0.529) was associated with a better outcome. These cardiac function parameters were incorporated in a modified disease-specific CVP Score. Patients with a mean modified cardiovascular profile score of ≤6 were over 3.7 times more likely to die than those with scores of 7–10. Conclusions: The original Cardiovascular Profile Score predicted the risk of death in right heart defects. The modified score was not validated as a good prediction tool by this study. Fetal RV pressure estimate and peak aortic velocity can be used as independent prognostic predictors.